Gender and Technology: A Bibliometric Analysis of Feminist Techno-Sociology Scholarship (2000–2024) - Elsa Fitriani; Rosidin, Rosidin; Fransiskus Novrianto Pakpahan; Rifai, Rifai (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Feminist techno-sociology critically examines the intersection of gender and technology, addressing how technological advancements both reinforce and challenge gendered power structures in labor, identity, and social relations; however, a systematic bibliometric analysis of this field remains scarce, creating a gap in understanding its intellectual evolution and global impact. This study fills that gap by employing bibliometric methods (co-citation and bibliographic coupling) to analyze 969 Scopus and Web of Science documents (2000–2024) from the UK, US, Brazil, Canada, and Indonesia, using VOSviewer to map citation networks and thematic trends. Key findings reveal four dominant research clusters: (1) sociology of knowledge and reflexivity, (2) social relations in professional roles, (3) Bourdieusian social reproduction, and (4) risk society and identity, with post-2010 scholarship emphasizing algorithmic bias, digital feminism (#MeToo), and inclusive tech design. The study underscores the urgency of interdisciplinary, gender-inclusive approaches in technology development while highlighting limitations such as Western-centric biases and overreliance on quantitative metrics. Future research should integrate postcolonial perspectives and qualitative methods to better address systemic inequalities, offering policymakers and scholars a foundation for equitable technological advancement.